Benefits of gum arabic supplementation to oral rehydration solution in managing acute diarrhea - Hasri Salwan; Isnada Isnada; Achirul Bakri; Rusdi Ismail; Erial Bahar (Indonesian Pediatric Society, 2007)
Background Oral rehydration solution (ORS) has been provensuccessfully to overcome dehydration in diarrhea. The improvementof the effectiveness of ORS is still needed to overcome some failures.Gum Arabic (GA), an indigestable starch, can enhance ORSabsorption in mice with diarrhea. It is worthy to explore its benefitsin human. Since GA is non toxic to human being, it is regardedethical to conduct effectiveness study directly in clinical setting.Objective To evaluate the effectiveness of GA supplementationto ORS in managing inpatients diarrheal cases .Methods A double blind clinical trial was conducted during Marchto September 2004 in the Department of Child Health of M. HoesinHospital, Palembang. The subjects were randomly enrolled to GA-ORS (GA) group or ORS (SO) group. Indirect measurements wereconducted on ORS absorptive enhancement by evaluating theduration of diarrhea after hospitalization, frequency of defecationduring hospitalization, ORS consumption during hospitalization,and time laps of stool consistency conversion. The effectivenessanalysis was controlled for confounders.Results Supplementation of 0.5 gram GA to 200 ml ORS could decreasethe duration of diarrhoea 15.65 hours (P=0.000) during hospitalisation,frequency of defecation during hospitalization 1.171 times/days(P=0.002), ORS consumption 38.39 ml/kg BW (P=0.029), time ofstool consistency to become semisolid 15.84 hours (P=0.000), andbecome solid 14.45 hours (P=0.002). Vomiting during hospitalizationand aged group of 6-11 months were significant confounder. However,after controlling the outcome with these confounding factors, thebenefits of GA supplementation were still significant.Conclusions GA supplementation to ORS significantly shortenthe duration of diarrhea, decreases the frequency of defecation,consumption of ORS, time of stool consistency to becomesemisolid and solid in inpatients diarrheal cases.